2019
DOI: 10.3748/wjg.v25.i28.3669
|View full text |Cite
|
Sign up to set email alerts
|

Importance of fatigue and its measurement in chronic liver disease

Abstract: The mechanisms of fatigue in the group of people with non-alcoholic fatty liver disease and non-alcoholic steatohepatitis are protean. The liver is central in the pathogenesis of fatigue because it uniquely regulates much of the storage, release and production of substrate for energy generation. It is exquisitely sensitive to the feedback controlling the uptake and release of these energy generation substrates. Metabolic contributors to fatigue, beginning with the uptake of substrate from the gut, the passage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 112 publications
3
64
0
4
Order By: Relevance
“…In the previous studies conducted in the USA, almost all domains are reported to be impaired except for abdominal symptoms and worry domains in patients with NAFLD, 20,34,35 and fatigue domain is the most impacted 34,36 . Thus, NAFLD is thought to be a symptomatic disease 20,34–36 . However, there were no available data for CLDQ‐NAFLD in Japanese patients.…”
Section: Cldq‐nafld/nash a Disease‐specific Instrument For Nafld/nashmentioning
confidence: 96%
See 1 more Smart Citation
“…In the previous studies conducted in the USA, almost all domains are reported to be impaired except for abdominal symptoms and worry domains in patients with NAFLD, 20,34,35 and fatigue domain is the most impacted 34,36 . Thus, NAFLD is thought to be a symptomatic disease 20,34–36 . However, there were no available data for CLDQ‐NAFLD in Japanese patients.…”
Section: Cldq‐nafld/nash a Disease‐specific Instrument For Nafld/nashmentioning
confidence: 96%
“…In patients with chronic liver disease, 50.0%–80.0% of patients are reported to have fatigue 36 . Fatigue domain is the most impacted domain in CLDQ‐NAFLD/NASH 20 .…”
Section: Cldq‐nafld/nash a Disease‐specific Instrument For Nafld/nashmentioning
confidence: 99%
“…Moreover, in the assessment of patients, it is important to acknowledge that NAFLD is also associated with a range of nonspecific physical and mental symptoms that can indirectly influence cognitive function [ 18 , 19 ]. Specifically, fatigue, that is a common complaint among patients with NAFLD and other liver diseases, can affect attention, concentration, and working memory [ 19 , 150 , 151 , 152 ]. In addition, NAFLD patients more frequently suffer from neuropsychiatric symptoms such as anxiety and depression that are also associated with impaired memory, attention, and executive function [ 153 , 154 , 155 ].…”
Section: Clinical Considerations and Future Perspectivesmentioning
confidence: 99%
“…We did not find any association between laboratory findings and physical function in the present cohort. Usually liver or kidney function may be related with fatigue, weakness, and decreased activity (21,22). Considering no relationship between organ and physical function in acute period after HSCT, decreased physical function may be originated from immobilization (23).…”
Section: Discussionmentioning
confidence: 99%